Beyond the Non-Proliferation Treaty. A Case Study of India, Pakistan and North Korea - Fiedler, Radosław (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
The main aim of the article is the presentation of important premises which were considered by these three states in conducting their military nuclear program. In the article both internal factors, such as political consolidation and strong society support, and external factors, such as deterrence and prestige were emphasised. For North Korea, nuclear weapons also became an attribute for gaining more international aid. The motives of India, North Korea and Pakistan for being a nuclear state are worrisome examples, because these three governments decided on nuclear weapons,,, despite the significant costs, such as sanctions, a risk of nuclear war or unstoppable arms race and the undermining of the non-proliferation regime.

Celem artykułu jest ukazanie głównych przesłanek jakimi rządy tych trzech państw kierowały się w rozwijaniu militarnego programu atomowego. W artykule zaakcentowano, że chodziło zarówno o czynniki wewnętrzne – konsolidacja polityczna, poparcie społeczne oraz zewnętrzne do których należały: odstraszanie oraz te związane z specyficzny sposób pojmowanym prestiżem. Dla Korei Północnej broń jądrowa stała się także atrybutem do uzyskania większej pomocy międzynarodowej. Motywy o proliferacji tych trzech państw stanowią przykład dość niepokojący, że ich rządy zdecydowały się na broń jądrową widząc w niej więcej korzyści, aniżeli kosztów związanych z sankcjami i ryzykiem konfliktu nuklearnego oraz wyścigu zbrojeń, nie mówiąc już o osłabieniu samego reżimu o nieproliferacji broni jądrowej.
Poza Układem o nieproliferacji broni jądrowej. Studium przypadku Indii, Pakistanu i Korei Północnej
Keywords: Non-proliferation Treaty; Układ o nieproliferacji; India; Indie; Pakistan; Pakistan; North Korea; Korea Północna